Media Representations of Urban Poverty in Jakarta and Manila: A Comparative Sociological Study - Dwi Retnani Srinarwati; Daniel Susilo; Nurannafi Farni Syam Maella; Akhmad Qomaru Zaman (Universitas Negeri Surabaya, 2026)
Urban poverty remains one of the most persistent social challenges in Southeast Asia, yet its portrayal in mainstream media often shapes public understanding and policy responses in unequal ways. While current scholarship acknowledges the media’s role in marginalization, there is a distinct lack of comparative research that details how divergent macro-level political economies produce specific, localized journalistic practices concerning the urban poor. This study addresses this gap by examining news and digital media in Jakarta and Manila, two megacities that embody contrasting trajectories of postcolonial urban development. Drawing on comparative sociological and critical discourse analyses, the research investigates narratives, visual framing, and thematic emphases across leading platforms between 2020 and 2025. Using mixed methods—including content analysis, interviews, and audience studies—the paper uncovers how journalistic practices produce different frames, ranging from moralized depictions of the poor as